2017
DOI: 10.1111/ecog.03093
|View full text |Cite
|
Sign up to set email alerts
|

Red squirrels decline in abundance in the boreal forests of Finland and NW Russia

Abstract: Recent global warming and other anthropogenic changes have caused well‐documented range shifts and population declines in many species over a large spatial extent. Most large‐scale studies focus on birds, large mammals, and threatened species, whereas large‐scale population trends of small to medium‐sized mammals and species that are currently of least concern remain poorly studied. Large‐scale studies are needed because on a smaller scale, important patterns may be masked by local variation and stochastic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
(125 reference statements)
3
10
0
Order By: Relevance
“…This study thus suggests that the synchrony is driven by fluctuating resources, and demonstrates how an explicit spatiotemporal approach can improve model performance for fluctuating populations. We also found that the red squirrel has declined in most parts of Finland for 29 years (see also Turkia et al 2018b). This is an important conservation message that highlights the urgent need for understanding the underlying causes behind population dynamics of the species.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This study thus suggests that the synchrony is driven by fluctuating resources, and demonstrates how an explicit spatiotemporal approach can improve model performance for fluctuating populations. We also found that the red squirrel has declined in most parts of Finland for 29 years (see also Turkia et al 2018b). This is an important conservation message that highlights the urgent need for understanding the underlying causes behind population dynamics of the species.…”
Section: Discussionsupporting
confidence: 62%
“…The data suggest a slightly decreasing trend for red squirrels throughout the study area, except for Southern Finland. A recent large-scale study from partially the same snow-track data (Turkia et al 2018b) as well as a diet analysis of red squirrel's predators (Selonen et al 2010) also suggested that the red squirrel has been declining. Turkia et al (2018b) showed that warming of winters is one reason behind the decline, but also that there are other, unknown reasons that were not found.…”
Section: Temporal Processesmentioning
confidence: 97%
See 2 more Smart Citations
“…The diurnal red squirrel is a far more common species than the flying squirrel, and it is wide-spread in temperate and boreal forest ecosystems throughout Eurasia, bur recent studies indicate that it also has been declining [ 27 , 40 ]. In boreal coniferous forests, the main food of the red squirrel is seeds of Norway spruce [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%